A Comparative Study on The Consolidation Test of Traditional and Non-Traditional Stabilized Peat - Ismail, Muhammad Aqil Hakimi; Abdul Halim, Mohammad Faris Mifzal; Mohd Nizam, Mohammad Afiq Haziq; Mohd Razali, Siti Nooraiin (Multidisciplinary Applied Research and Innovation, 2022)
Peat have been identified as highly organic soil, diverse mixture and undergo anaerobic condition at moderate and low temperature. The ojective of this study is to identify the settlement of original and stabilized peat. The effect of different types of stabilizers to the settlement properties of peat were observed. Two types of stabilizer used in this study which are polymer and cement. For comparison the settlement study also conducted for original peat. This study focused on the numerical study of peat settlement by using PLAXIS 2D.  The geometry model were designed in 2D and then converted to the finite element model for the analysis process. The next process was carried out to the calculation phase to produce the settlement value and graph for all samples. The result show that the settlement of original peat is higher compared to the stabilized peat. Meanwhile, the settlement of stabilized peat with polymer show the lower value. Thus, it is important to study the settlement of soil in order to predict the ability of soil to support structures.